Menstrual Disorders and its Effects on Academic Performance among the Nursing Students of PUSHS, Gothgaun - Shrestha, Sapana; Manandhar, Saraswati; Limbu, Chandrakala; Kunwar, Chanchala; Sinha, Pramila; Shrestha, Ramesh (Birat Journal of Health Sciences, 2022)
Introduction: Menstrual cycle is a periodic physiological process in women of childbearing age. Menstrual disorders may affect the daily activities and quality of life among reproductive age group women worldwide. Objective: The objective of this study was to find out the menstrual disorders and its effects on academic performance among the nursing students of Purbanchal University School of Health Sciences. Methodology: It was a descriptive, cross-sectional study conducted among 170 undergraduate nursing students of Purbanchal University School of Health Sciences, Gothgaun. Proportionate followed by simple random sampling (lottery method) was adopted. Data was collected through self administered method using semi structured questionnaire. Statistical analysis was done by descriptive and inferential statistics using SPSS version 16.0. Female with systemic health problems, any diagnosed pelvic pathology (fibroids, pelvic inflammatory disease), positive pregnancy test, and lactating mothers were excluded from the study. Results: Among 170 respondents, most of them (87.1%) had some form of premenstrual symptoms. Majority of them (77.6%) had dysmenorrhea. There was statistically significant association between dysmenorrhea and academic performance with class absenteeism (p=0.009), lack of concentration in class (p<0.001), not able to prepare for exam (p=0.014), mood swings (p=0.043), difficulty in participating in extracurricular activities and difficulty in public speaking (p=0.007). Premenstrual syndrome was also significantly associated with class absenteeism (p=0.012), sleeping desire during lectures (p=0.031) and mood swings (p=0.001). Conclusion: Menstrual disorders were significantly high among the nursing students and most of them were suffering from premenstrual syndrome and dysmenorrhea. It had significant impact on academic performance of nursing students.